Smartphone Sensor based applications for Internet of Things - Biwalkar, Ameyaa (International Journal of Advanced Science and Technology, 2019)
This paper presents two applications that help urban users for safe driving and smart home control. Nowadays, the vehicle manufacturers emphasize on the importance of safety with the help of various driver assistance systems. Also, the mobile smartphones are embedded with various sensors that can be used to record and analyze various driving behaviors of a driver. The smartphone can become a tool for storing as well as controlling data obtained from various IoT sensors. The sensors embedded in the mobile are used to record data for critical driving events. The analysis using Hidden Markov models (HMM) and Fuzzy logic can help to provide feedback to the users to avoid car accidents and to stimulate safe driving practices. The other application helps to improve and analyze the growth of potted plants with a smartphone using sensors and cloud services especially for urban users.